Processing and properties of nanostructured solid-state energy storage devices - Huang, C (2012)
A scalable spray processing technique was used to fabricate carbon nanotube (CNT)-based film electrodes and solid-state supercapacitors. The sprayed CNT-based electrodes comprised a randomly interconnected meso-porous network with a high electrical conductivity. Layer-by-layer (LbL) deposition of functionalised and oppositely charged single-wall carbon nanotubes (SWNTs) increased the electrode density and improved charging and discharging kinetics when compared with carboxylic functionalised only SWNT electrodes. The capacitance was further increased to 151 F g-1 at 2 mV s-1 and 120 F g-1 at 100 mV s-1 after vacuum and H2 heat treatments that removed the functional groups, and resulted in a hybrid microstructure of SWNTs and multi-layer graphene sheets from unzipped SWNTs. Flexible solid-state supercapacitors were fabricated by directly spraying multi-wall carbon nanotube (MWNT)-based aqueous suspensions onto both sides of a Nafion membrane and dried. A single cell with MWNT-only electrodes had a capacitance of 57 F g-1 per electrode at 2 mV s-1 and 44 F g-1 at 150 mV s-1. Cells with MWNT/ionomer electrodes showed a higher H+ mobility and a lower charge transfer resistance, and the capacitance increased to 145 F g-1 at 2 mV s-1 and 91 F g-1 at 150 mV s-1. Finally, MWNT/TiO2 nanoparticle/ionomer hybrid electrodes were used in the same solid-state supercapacitor configuration and provided a capacitance of 484 F g-1 per electrode at 5 mV s-1 and 322 F g-1 at 100 mV s-1. A qualitative model of the charge storage mechanism was developed, where TiO2 promoted H+ ions via redox reactions that fed protons into the proton-conducting ionomer coating over the MWNTs (in which the TiO2 was embedded), while electrons were readily conducted through the MWNT scaffold. This solid-state supercapacitor provided both attractive energy (31.8 Wh kg-1) and power (14.9 kW kg-1) densities, where such high energy density is difficult to achieve for MWNTs alone and such high power density is difficult for metal oxides alone, especially in the solid state.